Härnösand och E4:an - vägen som lokaliseringsfaktor - Wård, Lisa (2011)
Cities have always been founded on nodes of different roads.The city Harnosand was founded where the road along the coast of north Sweden meets the sea and the calm bay of Nattviken behind the island of Harnon. Harnosand has a big historic heritage as one of the first cities in the north part of Sweden, centre of the church and education city. The incrising centralisation of Sweden and the globalication of the world have made north of Sweden to the backside of Sweden.The coun- tryside and the smaller cities don ́t live anymore. In Harnosand is big moving out and many empty spaces. In the middle of Harnosand next to Nattviken, is one of these empty spaces. This empty space next to the road of E4, that leads out in the world and Europa. Can the space be used to promote the city, face the city towards the world and at the same time create a posi- tive experience for living people in the city? By looking at the different epocs of the cty to find out the identity of the city makes a try to mirror the his- tory in a park, Nattvikstrappen, on the empty space by Nattviken. Städer har uppstått i knutpunkter mellan olika farleder. Staden Härnösand kom att ligga där vägen längs Norrlandskusten mötte den lugna viken Nattviken bakom ön Harnön. Härnösand har ett stort historiskt arv, som en av Norrlands första städer, centrum for kyrkans makt och skolstad. Den ökade centralisering i Sverige och globaliseringen i världen har gjort Norrland till Sveriges baksida. Landsbygden och de mindre staderna lever inte längre. I Härnösand ar utflyttningen stor och ödetomterna gapar tomma. Mitt i Härnösand, vid Nattviken, finns en av dessa ödetomter. Ödetomten ligger bredvid E4:an, vägen som leder ut i världen och Europa. Kan tomten användas for att profilera staden, vända ansiktet utåt och samtidigt skapa en positiv upplevelse for de boende i staden? Genom att se på stadens olika tidsepoker for att ta reda på stadens identitet görs ett försok att spegla historien i en park, Nattvikstrappen, på ödetomten vid Nattviken.